ORGANIZATION OF COLLOBORATIVE LEARNING IN DEVELOPING SPEAKING SKILLS (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the organization and implementation of collaborative learning as a pedagogical approach for developing speaking skills among foreign language learners. Speaking is one of the most complex skills to master because it integrates linguistic competence, fluency, accuracy, and socio-pragmatic awareness. Traditional teacher-centered methods often fail to provide sufficient opportunities for authentic communication. Collaborative learning, on the other hand, encourages students to work interactively in pairs or groups to achieve shared goals, exchange feedback, and co-construct linguistic knowledge. Drawing on socio-cultural theory and the interaction hypothesis, this paper analyzes the main principles of collaborative learning, its advantages and limitations, and its contribution to enhancing speaking performance. Empirical evidence from recent studies confirms that students engaged in collaborative tasks show significant improvement in fluency, confidence, and communicative competence. The article concludes with methodological recommendations for teachers aiming to organize effective collaborative speaking activities in EFL classrooms.